PENGEMBANGAN PERANGKAT PEMBELAJARAN KONTEKSTUAL PADA MATERI PEMANASAN GLOBAL UNTUK KELAS XI SMA - Amirudhiniah Amirudhiniah; Muhammad Syafi'i; Zuhdi Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning tools developed are contextual learning tools on global warming material for class XI SMA, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Learning Outcomes Test. The purpose of this study was to determine the validity of contextual learning tools on global warming material. This type of research is research and development (R&D) with a 4D model. The instruments used were the RPP validation assessment sheet, LKPD, and the Learning Outcomes Test which were used by the validator to assess learning tools. The data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. Based on the results of the validity data analysis, the average validity of the RPP at the first and second meeting was 3.12 and 3.15 with the high category (T), the average validity of LKPD 01 and 02 was 3.04 and 3.07. with the high category (T), and the average validity of the Learning Outcomes Test of 3.05 with the high category (T). Thus the contextual learning tools developed are declared valid and suitable for use by senior high school students in class XI on global warming material.Key Words: Device development, Contextual Learning, Global Warming